Waqf Literacy, Islamic Religiosity, Subjective Norm, Perceived Behavior Control, and Attitude on Muhammadiyah Citizens' Interest in Becoming Wakif - Rini, Nova; Susilawati, Susi; Suryaningsih, Fina (Journal of Islamic Economic Laws, 2024)
Muhammadiyah citizens consisting of Muhammadiyah members and those who work and study or attend Muhammadiyah organizations. There are interesting objects to analyze because Muhammadiyah can collect waqf assets, especially cash waqf of Rp 2.4 trillion per year. This is a very large amount. If invested productively, the results or profits can be channelled for the progress and prosperity of the Muhammadiyah organization and Muslims. This research aims to determine the influence of the variables Waqf Literacy, Islamic Religiosity, Subjective Norm, Perceived Behavior Control, and Attitude in influencing the interest of Muhammadiyah citizens to become wakif. The analytical method used is quantitative with a Structural Equation Model (SEM) approach. The software used is SmartPLS 3.0. The sample used was 188 respondents from 14 provinces in Indonesia. This research indicates that Muhammadiyah citizens' interest in becoming wakif can be directly influenced by the variables of Islamic Religiosity and their Perceived Behavior Control (PBC). However, the indirect influence on Muhammadiyah's citizens' interest is insignificant. This result can be seen from the research results that the variables Islamic Religiosity, Waqf Literacy, Subjective Norm, PBC, and Attitude do not significantly influence the interest of Muhammadiyah citizens in becoming wakif. One of the causes of this insignificance is the direct influence between the Attitude variable and interest insignificantly. So, the implications of this research were increasing Islamic Religiosity and PBC in Muhammadiyah citizens becoming waqif. Implications for further research include adding or replacing variables that influence people's interest in becoming a waqif, are trust and transparency